2020
DOI: 10.1111/odi.13591
|View full text |Cite
|
Sign up to set email alerts
|

Finding distinctions between oral cancer and periodontitis using saliva metabolites and machine learning

Abstract: Objective The aim of this research is the study of metabolic pathways related to oral cancer and periodontitis along with development of machine‐learning model for elucidation of these diseases based on saliva metabolites of patients. Methods Data mining, metabolomic pathways analysis, study of metabolite–gene networks related to these diseases. Machine‐learning and deep‐learning methods for development of the model for recognition of oral cancer versus periodontitis, using patients' saliva. Results The most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 42 publications
0
30
0
2
Order By: Relevance
“…The majority of these studies used a convolutional neural network (CNN) [ 2 , 15 – 22 , 24 26 , 28 , 31 36 , 38 41 , 43 45 , 48 , 49 ]. Several data types such as gene expression data [ 15 , 45 ], spectra data [ 20 , 21 , 29 , 34 , 37 , 44 , 48 ], and other image data types—anatomical [ 16 ], intraoral [ 17 ], histology [ 18 , 27 ], auto-fluorescence [ 19 , 22 ], cytology-image [ 23 ], neoplastic [ 40 ], clinical [ 28 , 36 , 38 ], oral lesions [ 42 ], computed tomography images [ 24 26 , 33 , 35 , 41 , 49 ], clinicopathologic [ 2 ], saliva metabolites [ 31 ], histopathological [ 30 , 32 , 43 ], and pathological [ 39 ] images have been used in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies used a convolutional neural network (CNN) [ 2 , 15 – 22 , 24 26 , 28 , 31 36 , 38 41 , 43 45 , 48 , 49 ]. Several data types such as gene expression data [ 15 , 45 ], spectra data [ 20 , 21 , 29 , 34 , 37 , 44 , 48 ], and other image data types—anatomical [ 16 ], intraoral [ 17 ], histology [ 18 , 27 ], auto-fluorescence [ 19 , 22 ], cytology-image [ 23 ], neoplastic [ 40 ], clinical [ 28 , 36 , 38 ], oral lesions [ 42 ], computed tomography images [ 24 26 , 33 , 35 , 41 , 49 ], clinicopathologic [ 2 ], saliva metabolites [ 31 ], histopathological [ 30 , 32 , 43 ], and pathological [ 39 ] images have been used in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, specificity and accuracy were also used to demonstrate the performance of the deep learning model for prognostication in OSCC [ 23 ]. Other studies used either accuracy, C-index (concordance index), F1-score, or Dice similarity coefficient (Dsc) mean value as the performance metrics for reporting the potential benefits of the deep learning model [ 2 , 18 , 18 , 26 , 28 , 29 , 31 33 , 39 41 , 44 , 45 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, these models have assisted in the prediction of lymph node metastasis [27][28][29]76]. Besides, they have been reported to perform well in differentiating between precancerous and cancerous lesions [64,[77][78][79][80][81]. These models have been integrated to offer an automated diagnosis of oral cancer [24,64,82].…”
Section: Deep Learning For Oral Cancer: From Precise Diagnosis To Precision Medicinementioning
confidence: 99%
“…Furthermore, recent studies have identified important molecular mechanisms/signaling pathways in cancer development and progression [71,, and several pathway analysis methods have been reported to elucidate the true nature of cancer and identify drug targets by using features extracted from large-scale data. The methodology is correct, and several results have been published that have contributed greatly to the development of the field of oncology [139][140][141][142][143][144][145][146][147][148][149][150]. However, it should be adequately recognized that there are limitations to the results obtained by a dry lab approach, and it is important to validate the results obtained by the dry lab approach using appropriate wet lab experiments (cell-level studies or animal-level studies using mice).…”
Section: Application Of Machine Learning and Deep Learning Techniquesmentioning
confidence: 99%